If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(2x-1)-2=13
We simplify the equation to the form, which is simple to understand
3(2x-1)-2=13
Reorder the terms in parentheses
+(+6x-3)-2=13
Remove unnecessary parentheses
+6x-3-2=+13
We move all terms containing x to the left and all other terms to the right.
+6x=+13+3+2
We simplify left and right side of the equation.
+6x=+18
We divide both sides of the equation by 6 to get x.
x=3
| 302-2a=210 | | 3/4m-5-1/2m | | 2-1/2=x | | m+4-4m+3= | | (x+2.1)-(0.1x+3)=11 | | x-10403=116 | | 5b=3.55 | | -22+6x=44-5x | | 4x-5=4x+7 | | 4x+5=4x+5 | | 3/2a-14=75 | | (x+2.7)-(0.3x+4)=11 | | -15-v=-24 | | y-2=5/4x | | 6(5-x)-12=2x-3(4+x) | | y=0.25x+21 | | 5n+20=n-24 | | 3p-6=13-4p | | 3(2x+5)=7-(2x) | | n/17=18 | | Dover-8.4=10.2 | | -11n=-154 | | 62.9296x+64.9278y=63.546 | | 1/8(5x-24) | | x^2+7x+35=0 | | 2/7=1/3+a | | 0.25= | | 1023/80=-3/3/10(-3/2+x) | | 3x+3=-3x-12 | | 3p=8p-r | | b+1/6=65 | | 36-7n=1+3(8-6n) |